Modern weapons and military equipment for issue 4-2016 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Holsters for pistols - standards purposes, use: The importance of tactical holster as part of tactical equipment, types and standards of construction and use.